Adolescent puerpera perceptions concerning nursing care in rooming-in facility - Nóbrega, Líbne Lidianne da Rocha e; Bezerra, Fernanda Patrícia Fernandes (Rev Rene, 2010)
The present study intended to know perceptions of puerpera adolescent about nursing care in Rooming-in facility (RI). This exploratory research, of a qualitative approach, was done at a philanthropic maternity hospital in Mossoró, RN, through semi-structured interviews with 10 parity adolescents in July, 2009. The found data about nursing care in RI were organized by categories that are sometimes relative to positive conceptions about nursing care, mainly to the drug administration, and sometimes they express the absence of professional monitoring and the wish of a private place to the adolescent mothers. It follows that there are ambiguity feelings among the puerpera adolescents that can be associated to the necessity of a systemized nursing care in RI, to the little experience of the adolescents and to the uncertainties of puerperal period.